2008
DOI: 10.2172/945434
|View full text |Cite
|
Sign up to set email alerts
|

Radiation shielding for superconducting RF cavity test facility at A0

Abstract: The results of Monte Carlo radiation shielding study performed with the MARS15 code for the vertical test facility at the A0 north cave enclosure at Fermilab are presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Analytical formulae, RF solvers and Monte Carlo codes have been traditionally used 1,2 to address various questions involving dark current from cavities. Generally only a few cavities are simulated and geometries are simplified, or the calculations focus only on beam dynamics.…”
Section: Scheme To Compute Radiation Fields At Lcls-ii Cryomodulesmentioning
confidence: 99%
“…Analytical formulae, RF solvers and Monte Carlo codes have been traditionally used 1,2 to address various questions involving dark current from cavities. Generally only a few cavities are simulated and geometries are simplified, or the calculations focus only on beam dynamics.…”
Section: Scheme To Compute Radiation Fields At Lcls-ii Cryomodulesmentioning
confidence: 99%
“…The study was performed using MARS15 Monte Carlo code [5] adopting the results from Fishpact simulations as the source term to provide spatial, energy and angular distributions of field emitted electrons inside the cavity. The study showed the need for additional shielding and as per the recommendations of the radiation safety committee interlocks were placed at the vulnerable locations (shown by simulations) to shut off the RF power in the event of radiation intensity nearing the cut off levels.…”
Section: Radiation Considerationsmentioning
confidence: 99%